2013
DOI: 10.1016/j.jmr.2013.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Temporal phase correction of multiple echo T2 magnetic resonance images

Abstract: Typically, magnetic resonance imaging (MRI) analysis is performed on magnitude data, and multiple echo T 2 data consist of numerous images of the same slice taken with different echo spacing, giving voxel-wise temporal sampling of the noise as the signals decay according to T 2 relaxation. Magnitude T 2 decay data has Rician distributed noise which is characterized by a change in the noise distribution from Gaussian, through a transitional region, to Rayleigh as the signal to noise ratio decreases with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…This results in a nonlinear problem; however, when the phase changes linearly with time, the ML estimator can be efficiently implemented using the Fast Fourier Transform (FFT). This case is of special interest, as linear phase variations were observed in the in vivo data used both in this paper and in [16].…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…This results in a nonlinear problem; however, when the phase changes linearly with time, the ML estimator can be efficiently implemented using the Fast Fourier Transform (FFT). This case is of special interest, as linear phase variations were observed in the in vivo data used both in this paper and in [16].…”
Section: Introductionmentioning
confidence: 81%
“…A few suggestions on how to solve this sub-optimality problem are available in the literature [14,15], where the authors apply maximum likelihood (ML) methods, taking the Rice distribution into account; however, these approaches are nonlinear and rather involved, which complicates the implementation and can lead to convergence problems. To make the problem more tractable, many algorithms for T 2 estimation are based on minimizing the LS criterion; however, it has been suggested that LS-based approaches can lead to tissue mischaracterization caused by the Rician noise [16]. Another approach, that was applied in [17], estimates the signal decay and the noise properties from the magnitude images, and uses this information to transform the magnitude data into a Gaussian signal that can be used for T 2 estimation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, N was set to 96 and echoes 97 to 128 were not used to avoid analysis artifacts that can be caused by the Rician noise floor. 28 In addition, M ¼ 120 logarithmically spaced T2 bins ranging from 8.25 ms (1.5× shortest echo time) to 1056 ms (2× longest echo time) were used to model the T2 decay in each voxel. The T2 − s j combinations for every voxel were stored independently as T2 distributions, and also summed together to create a T2 distribution histogram for the entire MR slice.…”
Section: T2 Decay Analysismentioning
confidence: 99%